RAMSAY HUNT SYNDROME SECONDARY TO DENTAL EXTRACTION - Waleem, Sheikh Saadat Ullah; Ashraf, Tanveer; Babar, Zaheer Uddin (Pakistan Armed Forces Medical Journal, 2018)
Ramsay Hunt syndrome, also known as geniculate neuralgia or nervus intermedius neuralgia is defined as an acute peripheral facial neuropathy associated with erythematous vesicular rash of skin of ear canal, auricle (also termed herpes zoster oticus), and/or mucous membrane of the oropharynx. The varicella zoster virus may involve multiple cranial nerves in addition to the facial nerve such as VIII, IX, V, and VI. We present a case of Ramsay Hunt Syndrome that developed after upper molar tooth extraction of the same side.An eleven years old child presented to us with history of heaviness of right side of face and inability to close his right eye for the past 01 day. The child had an impacted upper molar tooth extraction on the same side under local anesthesia (2% lignocaine + 1:100000 adrenaline) by the dental surgeon 02 days ago. Approximately 24 hours after the dental extraction his parents noticed asymmetry of the face with deviation of the angle of mouth to left and inability to close the right eye completely and the child was brought to us.